Investigation of Emulsion Bitumen Adhesion to Aggregates in Chipseal at Various Temperatures for Low-Cost Pavement Management - Khabiri, Mohammad Mehdi; Poya Sadeghi; Ansari, Omid (International Journal of Sustainable Construction Engineering and Technology, 2021)
Preventive maintenance is recommended by economic models in pavement management. One of the issues that the Chipseal mix is currently dealing with is the degree of separation of the material from the mixture's surface due to a lack of proper adhesion between the emulsion(green) bitumen, and the aggregate. Have and cause an accident. In this study, it was attempted to reduce material separation by increasing the percentage of bitumen in the mixture as well as the percentage of sand as a filler. The results of this study showed that with increasing the percentage of emulsion bitumen in the chipseal mixture and with it increases the percentage of filler in the mixture, the separation rate of aggregates to less than 10% in the temperature range of -15 to +45 Â° C, and a Created a more cohesive mixture.